Pengaruh Kualitas SDM, Pemanfaatan Sistem Informasi, Pengendalian Intern dan Komitmen Organisasi Pada Kualitas Laporan Keuangan - Shintia, Cok Istri Prami; Erawati, NI Made Adi (E-Jurnal Akuntansi, 2017)
This study aims to examine the influence of human resource quality, utilization of information systems, internal control systems and organizational commitment on the quality of financial statements of the Regional Government of Klungkung Regency. The respondents were 3 people, namely the Head of Sub Division of Finance, Treasurer and Staff of Sub Division of Finance in each SKPD of Klungkung Regency which amounted to 60 respondents. This research uses primary data and tested with descriptive statistical test, validity test, reliability test, multiple regression analysis, normality test, heteroscedasticity test, R² test, F test and T test. The result of analysis shows that quality of human resources, utilization of informan system, internal control system and Organizational commitment has a positive effect on the quality of local government financial reports. The conclusion of the analysis is the higher the quality of human resources, Utilization of Information Systems, Internal Control System and Organizational Commitment owned by employees in SKPD Klungkung District in carrying out a task to make financial reports, the ability to make financial reports will be better.